2017
DOI: 10.1080/17538947.2017.1351583
|View full text |Cite
|
Sign up to set email alerts
|

Geospatial web services pave new ways for server-based on-demand access and processing of Big Earth Data

Abstract: (2018) Geospatial web services pave new ways for server-based on-demand access and processing of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 22 publications
0
25
0
Order By: Relevance
“…In the context of geo-data analysis, a wide range of various web services are already available, such as those provided by the Open Geospatial Consortium. There are also several other web-based systems that provide tools to search, order, and download RS data; these include the USGS Earth Explorer [228] for data analysis, the National Climatic Data Center-NCDC Climate WebGIS (http://www.climate.gov/#dataServices), the NASA Giovanni [229] or the Eearth Observation Data Service (http://www.earthserver.eu/services/eods) for the RS community, the PlanetServer for the Planetary science community [230], and single web services and free software solutions for automatically generated 3D point clouds for UAVs [231]. Eberle et al [232] demonstrated how different web services can be embedded to generate a geo-data toolbox for monitoring forest in Siberia using RS data.…”
Section: Handling Petabyte-scale Rs Data With Cloud and Web Servicesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of geo-data analysis, a wide range of various web services are already available, such as those provided by the Open Geospatial Consortium. There are also several other web-based systems that provide tools to search, order, and download RS data; these include the USGS Earth Explorer [228] for data analysis, the National Climatic Data Center-NCDC Climate WebGIS (http://www.climate.gov/#dataServices), the NASA Giovanni [229] or the Eearth Observation Data Service (http://www.earthserver.eu/services/eods) for the RS community, the PlanetServer for the Planetary science community [230], and single web services and free software solutions for automatically generated 3D point clouds for UAVs [231]. Eberle et al [232] demonstrated how different web services can be embedded to generate a geo-data toolbox for monitoring forest in Siberia using RS data.…”
Section: Handling Petabyte-scale Rs Data With Cloud and Web Servicesmentioning
confidence: 99%
“…Eberle et al [232] demonstrated how different web services can be embedded to generate a geo-data toolbox for monitoring forest in Siberia using RS data. Other novel developments of geospatial web services are oriented toward a server-based on-demand access and processing of big Earth data [230]. These web services are suitable for monitoring platforms such as tablets for better managing forest health inventory data, where on-demand RS and geo-data are essential.…”
Section: Handling Petabyte-scale Rs Data With Cloud and Web Servicesmentioning
confidence: 99%
“…The term Big Earth Data (Guo, Wang, Chen, & Liang, 2014;Guo, Wang, & Liang, 2016) has been used to refer to large volumes of Earth observation data collected from satellites. This term has also been used to refer to any available geospatial data, including ground-based sensors and large computational model systems such as Numerical Weather Prediction (NWP) (Wagemann, Clements, Figuera, Rossi, & Mantovani, 2017). Platforms serving Big Earth Data face the added challenge of not only having to store, manage and process large collections of data, but they also need to provide interfaces for users to access the data.…”
Section: Introductionmentioning
confidence: 99%
“…We start with the paper entitled 'Geospatial web services pave new ways for server-based on-demand access and processing of Big Earth Data'. Wagemann et al (2018) advocate in their paper a transfer of traditional data analysis workflows into service-oriented workflows. They demonstrate that web services have the potential to mitigate limitations of Big Earth Data analyses caused by restricted storage space and processing power at the user side.…”
Section: Innovation In Geoprocessing For a Digital Earthmentioning
confidence: 99%
“…They demonstrate that web services have the potential to mitigate limitations of Big Earth Data analyses caused by restricted storage space and processing power at the user side. Wagemann et al (2018) show four applications using standardized web services, more specifically Web Coverage Services (WCS) 2.0 and Web Coverage Processing Services, in marine, climate, planetary and Earth observation sciences. They complement the demonstration of the applications with a discussion of benefits and challenges for data providers, technical users and end users or decision makers.…”
Section: Innovation In Geoprocessing For a Digital Earthmentioning
confidence: 99%